ANALISIS STRUKTUR LINGUISTIK BAHASA: FONOLOGI, MORFOLOGI, SINTAKSIS, DAN SEMANTIK - Atika Hafizah; Dia Rahmadini; Via Gusnida; Silvina Noviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Modern linguistic studies view language as a system composed of several layers of structure: phonology, morphology, syntax, and semantics. These four aspects are interconnected in forming meaningful utterances that can be understood by both speakers and listeners. This study examines in depth how each language structure works, from sound formation to more complex meaning construction. A literature review method was used to examine linguistic theories from various influential international sources. The analysis shows that a comprehensive understanding of linguistic structure is important not only for language research but also for linguistics teaching, language education policy development, and discourse analysis practices. Overall, this study confirms that language is a multi-layered system with regular internal patterns that can be analyzed scientifically.